Old Meets New: The Former Kemajoran Airport - Diptya Anggita; Ashri Prawesthi D; Rafli Alfiano (International Journal of Glocal Tourism, 2021)
Purpose: This research tries to preserve cultural building heritage by reusing old buildings as The National Gallery of Indonesia’s Satellites (Galeri Nasional Indonesia Satelit) to provide design recommendations that can combine old and contemporary aspects. Research methods: This research is divided into three stages: data exploration and observation of the existing building; activities of reviewing data and making 3D models of existing building; and analysis using the theory of “The 10 Trends of Museum” to create a new attraction for a gallery. Findings: The former Kemajoran Airport has several potentials which are maintained as the identity and uniqueness of the building. The implementation of the theory can find out where the best location to display artwork according to its type and how to display it. The initial stage in utilizing old building is understanding the history, existing conditions, and potential of the building. Implication: The latest trends can attract the wider community to visit exhibition in gallery, especially the current generation. It can be used as one of the tourist destinations in Indonesia.